FAKTOR-FAKTOR PENENTU STRUKTUR MODAL PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wulansari Dewi; Henny Setyo Lestari (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2014)
This research discusses whether there are effect of capital structure on leverage. Independentvariable consist of firm size, firm growth, tangibility of assets, profitability, and risk. Dependentvariable divided into 3 indicators such as total debt ratio, long term debt ratio, and short termdebt ratio. The study consisted of 164 nonfinancial industries, which was obtained from officialwebsite of Indonesia Stock Exchange (http://www.idx.co.id). The sampling method used in thisstudy was purposive sampling and data analysis method used for hypothesis testing is linearregression analysis. The results of hypothesis testing showed that there is influence betweencapital structure on total debt ratio and short term debt ratio. But not too significantly to longterm debt ratio. The contribution of this study hopefully can help managers and investors aliketo make a right decision in nonfinancial industry in Indonesia.Keywords: capital structure, growth, long term debt ratio, risk, ROA, short term debtratio, size,tangibility of assets, total debt ratio.